Analisis Pemanfaatan Sampah Organik Untuk Briket Arang Ramah Lingkungan Untuk Meningkatkan Ketahanan Energi : Studi Kasus Di Perlis, Malaysia - Harahap, Raja; Parinduri, Luthfi; Widya, Helma; Simbolon,, Ronald HT; Nasution, Suhela Putri (Jurnal Masyarakat Indonesia (Jumas), 2025)
This article presents an innovative approach to addressing energy security through the production of environmentally friendly charcoal briquettes derived from organic waste. Held on February 18, 2025, at the UniMAP Rectorate Building in Perlis, Malaysia, the event aimed to explore sustainable energy alternatives by utilizing organic waste materials to produce environmentally friendly and energy-efficient charcoal briquettes. This study evaluated the technical feasibility, environmental impact, and potential benefits of utilizing organic waste as a renewable energy source. Through a series of interactive discussions and practical demonstrations, the event highlighted the importance of circular economy practices and sustainable energy solutions to mitigate the global energy crisis and environmental challenges.